Revisiting Intensity Interferometry Using Picosecond Timescale Resolution - Camarata, Matthew A.; Horch, E. P. (Bulletin of the American Astronomical Society, 2011)
After the success of Hanbury Brown, Davis, and their collaborators in measuring all stellar diameters resolvable by the 166-m interferometer at Narrabri nearly four decades ago, research into optical intensity interferometry was largely discontinued. Signal-to-noise ratios and timing resolutions limited the technique to relatively bright stars over a narrow bandwidth. Modern photon-correlation electronics, however, may help to revive the technique, allowing for increased temporal resolution and longer baselines. In this paper, the PicoHarp 300 Time-Correlated Single Photon Counting System is characterized in order to demonstrate its ability to perform interferometric measurements. Time correlations of coherent and incoherent source apertures are measured and their autocorrelations compared with theory. The speed of light is also directly measured using the shift in temporal correlation between offset detectors. Finally, the possibility of two independent systems, linked between two large-aperture telescopes, is discussed with the goal of determining whether longer baselines can be achieved.
Keywords: dept.phy; ⛔ No DOI found

Optimizing Speckle Data Reduction for Analysis of Faint Sources - Gaulin, Joseph; Horch, E.; Howell, S.; Ciardi, D. (American Astronomical Society, AAS Meeting, 2011)
Electron-multiplying CCD cameras are now being widely used in speckle imaging, and have been shown to deliver excellent photometric precision under good observing conditions. Successful image reconstructions have been made on binary stars fainter than 14th magnitude. However, improving the speckle signal-to-noise ratio and the fidelity of image reconstructions for faint sources would be extremely helpful in several areas of research where diffraction-limited images are required, including our own ongoing speckle observations of Kepler exoplanet candidate stars using the WIYN Telescope at Kitt Peak. In this paper, we investigate (1) robust cosmic ray rejection and (2) removal of low signal-to-noise frames as two ways to maximize data quality for faint source observations. Cosmic ray rejection is not normally a major concern in speckle imaging due to the brightness of the targets traditionally observed and the short frame times. Nonetheless, when imaging faint targets, more frames are needed to achieve a given signal-to-noise ratio, increasing the chance of cosmic ray events on the detector, and even a single cosmic ray hit in the frame sequence can significantly affect the source detection ability and photometry obtained in the observation. Similarly, faint sources often exhibit some frames with a well-defined image core while in other frames it is difficult to tell if the source is even present, primarily due to seeing variation during the observation. A new speckle reduction algorithm has been created that removes cosmic rays without throwing out frames and rejects frames with bad seeing, and its performance is investigated to determine to what extent this can improve source detection and photometric reliability in the final reconstructed image. Funding for this work was provided by the Kepler Science Center and by NSF Grant AST-0908125.
Keywords: dept.phy

Minor Planet Observations with the Differential Speckle Survey Instrument - Bouvier, Jean-Claude; Horch, E. (American Astronomical Society, AAS Meeting, 2011)
The Differential Speckle Survey Instrument (DSSI) is a dual-channel speckle imaging system that takes speckle patterns in two colors simultaneously using two electron-multiplying CCD cameras. The system has been shown to deliver excellent photometry of binary stars under good observing conditions, which raises the question of whether results of similar quality can be obtained on extended objects such as minor planets, and if so, to what limiting magnitude. In this study, we present speckle image reconstructions of images of 2 Pallas, 216 Kleopatra, and 283 Emma made from data taken at the WIYN 3.5-m Telescope at Kitt Peak. We compare two different phase reconstruction algorithms: (1) an iterative technique, and (2) a relaxation technique. Since Pallas is a flattened disk, Kleopatra has a dumbbell shape, and Emma is a binary asteroid with known orbital parameters, these three targets represent three distinct image morphologies that allow for a robust comparison of the two phase reconstruction programs. Prospects for future work in this area with DSSI are discussed. This work is funded by NSF grant AST-0908125.
Keywords: dept.phy

Speckle Observations of Binary Stars with the Wiyn Telescope. Vii. Measures During 2008-2009 - Horch, Elliott P.; Bahi, Lizzie Anne P.; Gaulin, Joseph R.; Howell, Steve B.; Sherry, William Henry; Gallé, Roberto Baena; van Altena, William F. (The Astronomical Journal, 2011)
Five hundred thirty-one speckle measures of binary stars are reported. These data were taken mainly during the period 2008 June through 2009 October at the WIYN 3.5m Telescope at Kitt Peak and represent the last data set of single-filter speckle observations taken in the WIYN speckle program prior to the use of the current two-channel speckle camera. The astrometric and photometric precision of these observations is consistent with previous papers in this series: we obtain a typical linear measurement uncertainty of approximately 2.5mas, and the magnitude differences reported have typical uncertainties in the range of 0.1-0.14 mag. In combination with measures already in the literature, the data presented here permit the revision of the orbit of A 1634AB (= HIP 76041) and the first determination of visual orbital elements for HDS 1895 (= HIP 65982).
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Kepler-18b, c, and d: a system of three planets confirmed by transit timing variations, light curve validation, warm-spitzer photometry, and radial velocity measurements* - Cochran, William D.; Fabrycky, Daniel C.; Torres, Guillermo; Fressin, Francois; Désert, Jean-Michel; Ragozzine, Darin; Sasselov, Dimitar; Fortney, Jonathan J.; Rowe, Jason F.; Brugamyer, Erik; Bryson, Stephen T.; Carter, Joshua A.; et al. (Astrophysical Journal Supplement Series, 2011)
We report the detection of three transiting planets around a Sun-like star, which we designate Kepler-18. The transit signals were detected in photometric data from the Kepler satellite, and were confirmed to arise from planets using a combination of large transit-timing variations (TTVs), radial velocity variations, Warm-Spitzer observations, and statistical analysis of false-positive probabilities. The Kepler-18 star has a mass of 0.97 M ⊙, a radius of 1.1 R ⊙, an effective temperature of 5345K, and an iron abundance of [Fe/H] = +0.19. The planets have orbital periods of approximately 3.5, 7.6, and 14.9 days. The innermost planet "b" is a "super-Earth" with a mass of 6.9 ± 3.4 M ⊕, a radius of 2.00 ± 0.10 R ⊕, and a mean density of 4.9 ± 2.4gcm3. The two outer planets "c" and "d" are both low-density Neptune-mass planets. Kepler-18c has a mass of 17.3 ± 1.9 M ⊕, a radius of 5.49 ± 0.26 R ⊕, and a mean density of 0.59 0.07gcm 3, while Kepler-18d has a mass of 16.4 ± 1.4 M ⊕, a radius of 6.98 ± 0.33 R ⊕ and a mean density of 0.27 ± 0.03gcm3. Kepler-18c and Kepler-18d have orbital periods near a 2:1 mean-motion resonance, leading to large and readily detected TTVs. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-18, KIC 8644288, 2MASS J19521906+4444467); techniques: photometric; techniques: spectroscopic

Origin of 90° domain wall pinning in Pb(Zr0.2Ti0.8)O3 heteroepitaxial thin films - Su, Dong; Meng, Qingping; Vaz, Carlos A. F.; Han, Myung-Geun; Segal, Y.; Walker, Fred; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H. (Applied Physics Letters, 2011)
We describe a transmission-electron-microscopy study of the ferroelectric domains in an epitaxial Pb(Zr0.2Ti0.8)O3 (PZT) film grown on La0.7Sr0.3MnO3/SrTiO 3(001). We directly observe the pinning of 90 domain walls by pairs of misfit dislocations, respectively, with Burgers vectors a [100] and a [001]. Model calculations based on the elastic theory confirm our finding that, in addition to the depolarization field surrounding the dislocation, the strain field of misfit dislocation-pairs plays the primary role in the formation and pinning of a domains. © 2011 American Institute of Physics.
Keywords: Depolarization fields; Domain walls; Domain-wall pinning; Elastic theory; Epitaxial growth; Ferroelectric domains; Ferroelectricity; Heteroepitaxial thin films; Heterojunctions; Lanthanum compounds; Lead; Manganese oxide; Model calculations; PZT; Strain fields; Zirconium; dept.phy

Domain pinning and valence state switching in Pb(Zr0.2Ti0.8)O3/La0.8Sr0.2MnO3 heterostructures - Su, Dong; Vaz, Carlos A. F.; Segal, Y.; Walker, Fred; Ahn, Chong H.; Han, M-G; Sawicki, Monica; Broadbridge, Christine (Microscopy and Microanalysis, 2011)
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. III. measures below the diffraction limit of the WIYN telescope - Horch, Elliott P.; van Altena, William F.; Howell, Steve B.; Sherry, William Henry; Ciardi, David R. (The Astronomical Journal, 2011)
In this paper, we study the ability of CCD- and electron-multiplying-CCD- based speckle imaging to obtain reliable astrometry and photometry of binary stars below the diffraction limit of the WIYN 3.5 m Telescope. We present a total of 120 measures of binary stars, 75 of which are below the diffraction limit. The measures are divided into two groups that have different measurement accuracy and precision. The first group is composed of standard speckle observations, that is, a sequence of speckle images taken in a single filter, while the second group consists of paired observations where the two observations are taken on the same observing run and in different filters. The more recent paired observations were taken simultaneously with the Differential Speckle Survey Instrument, which is a two-channel speckle imaging system. In comparing our results to the ephemeris positions of binaries with known orbits, we find that paired observations provide the opportunity to identify cases of systematic error in separation below the diffraction limit and after removing these from consideration, we obtain a linear measurement uncertainty of 3-4 mas. However, if observations are unpaired or if two observations taken in the same filter are paired, it becomes harder to identify cases of systematic error, presumably because the largest source of this error is residual atmospheric dispersion, which is color dependent. When observations are unpaired, we find that it is unwise to report separations below approximately 20 mas, as these are most susceptible to this effect. Using the final results obtained, we are able to update two older orbits in the literature and present preliminary orbits for three systems that were discovered by Hipparcos. © 2011. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Observations of Binary Stars with the Differential Speckle Survey Instrument. II. Hipparcos Stars Observed in 2010 January and June - Horch, Elliott P.; Gomez, Shamilia C.; Sherry, William Henry; Howell, Steve B.; Ciardi, David R.; Anderson, Lisa M.; van Altena, William F. (The Astronomical Journal, 2011)
The results of 497 speckle observations of Hipparcos stars and selected other targets are presented. Of these, 367 were resolved into components and 130 were unresolved. The data were obtained using the Differential Speckle Survey Instrument at the WIYN 3.5 m Telescope. (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, YaleUniversity, and theNational Optical AstronomyObservatories.) Since the first paper in this series, the instrument has been upgraded so that it now uses two electron-multiplying CCD cameras. The measurement precision obtained when comparing to ephemeris positions of binaries with very well known orbits is approximately 1-2 mas in separation and better than 0.̊ 6 in position angle. Differential photometry is found to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We derive preliminary orbits for two systems. © 2011. The American Astronomical Society.
Keywords: Binaries: Visual; Techniques: High angular resolution; Techniques: Interferometric; Techniques: Photometric; dept.phy; peer-reviewed

Team-based interdisciplinary materials research using image processing - Garofano, Jacquelynn; Sadowski, Thomas; DaPonte, John S.; Broadbridge, Christine (2011)
There is an acute and well-documented need for image processing of microscopy data in materials science regarding, for example, the characterization of the structure/property relationship of a given materials system. In our work, image processing has been used as a framework for conducting interdisciplinary team-based research that effectively integrates programs within the Center for Research on Interface Structures and Phenomena (CRISP) Materials Research Science and Engineering Center (MRSEC), e.g. research experiences for undergraduates (REU), teachers (RET) and high school fellowships. This research resulted from a five-year long collaboration between CRISP and the Physics and Computer Science Departments at Southern Connecticut State University (SCSU). This paper will focus on the implementation of team-based research experiences as a vehicle for interdisciplinary science and education. Representative results of several of the studies are presented and discussed. © 2011 Materials Research Society.
Keywords: Characterization; Engineering research; High school; Image processing; Interface structures; Interfaces (materials); Materials research; Materials systems; Research experience; Science and engineering; dept.phy

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b, KIC 10264660, 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Kepler-15b: A hot jupiter enriched in heavy elements and the first kepler mission planet confirmed with the hobby-eberly telescope - Endl, Michael; Macqueen, Phillip J; Cochran, William D; Brugamyer, Erik; Buchhave, Lars A; Rowe, Jason F; Lucas, P W; Isaacson, Howard; Bryson, Steve; Howell, Steve B; Fortney, Jonathan J; Hansen, Terese; et al. (Astrophysical Journal Supplement Series, 2011)
We report the discovery of Kepler-15b (KOI-128), a new transiting exoplanet detected by NASA's Kepler mission. The transit signal with a period of 4.94days was detected in the quarter 1 (Q1) Kepler photometry. For the first time, we have used the High Resolution Spectrograph (HRS) at the Hobby-Eberly Telescope (HET) to determine the mass of a Kepler planet via precise radial velocity (RV) measurements. The 24 HET/HRS RVs and 6 additional measurements from the Fibre-fed chelle Spectrograph spectrograph at the Nordic Optical Telescope reveal a Doppler signal with the same period and phase as the transit ephemeris. We used one HET/HRS spectrum of Kepler-15 taken without the iodine cell to determine accurate stellar parameters. The host star is a metal-rich ([Fe/H]= 0.36 ± 0.07) G-type main-sequence star with Teff = 5515 ± 124 K. The semi-amplitude K of the RV orbit is 78.7+8.5 -9.5ms-1, which yields a planet mass of 0.66 ± 0.1 M Jup. The planet has a radius of 0.96 ± 0.06R Jup and a mean bulk density of 0.9 ± 0.2 gcm-3. The radius of Kepler-15b is smaller than the majority of transiting planets with similar mass and irradiation level. This suggests that the planet is more enriched in heavy elements than most other transiting giant planets. For Kepler-15b we estimate a heavy element mass of 30-40 M ⊕. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-15, KOI-128, KIC 11359879, 2MASS J19444814+4908244); techniques: image processing; techniques: photometric; techniques: radial Velocities; techniques: spectroscopic

The WIYN Speckle Survey: Toward the Thin and Thick Disk Binary Populations - Horch, Elliott P.; van Altena, William F.; Docobo, J. A.; Tamazian, V. S.; Balega, Y. Y. (INTERNATIONAL WORKSHOP ON DOUBLE AND MULTIPLE STARS: DYNAMICS, PHYSICS, AND INSTRUMENTATION, 2011)
The WIYN Observatory speckle program has been in operation since 1997, taking data mainly with a large-format, low-noise CCD detector. However, new instrumentation, first used in 2008, has created the possibility to use two detectors simultaneously, collecting light in two different filters. The program also now has access to two electron-multiplying CCD cameras, which dramatically improve the limiting magnitude of the diffraction-limited imaging capabilities. The application of this instrumentation to an ongoing survey of the Hipparcos Double Stars and other projects is discussed. © 2011 American Institute of Physics.
Keywords: binaries: visual; dept.phy; stars: stellar populations; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Speckle camera observations for the NASA kepler mission follow-up program - Howell, Steve B; Everett, Mark E; Sherry, William Henry; Horch, Elliott P; Ciardi, David R (The Astronomical Journal, 2011)
We present the first results from a speckle imaging survey of stars classified as candidate exoplanet host stars discovered by the Kepler mission. We use speckle imaging to search for faint companions or closely aligned background stars that could contribute flux to the Kepler light curves of their brighter neighbors. Background stars are expected to contribute significantly to the pool of false positive candidate transiting exoplanets discovered by the Kepler mission, especially in the case that the faint neighbors are eclipsing binary stars. Here, we describe our Kepler follow-up observing program, the speckle imaging camera used, our data reduction, and astrometric and photometric performance. Kepler stars range from R = 8 to 16 and our observations attempt to provide background non-detection limits 5-6mag fainter and binary separations of ∼0.05-2.0 arcsec. We present data describing the relative brightness, separation, and position angles for secondary sources, as well as relative plate limits for non-detection of faint nearby stars around each of 156 target stars. Faint neighbors were found near 10 of the stars. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; instrumentation: high angular resolution; peer-reviewed; planets and satellites: general; techniques: photometric